2002
DOI: 10.1039/b111563b
|View full text |Cite
|
Sign up to set email alerts
|

Oxide solubility and Raman spectra of NdF3–LiF–KF–MgF2–Nd2O3 melts

Abstract: The solubility of Nd 2 O 3 in NdF 3 -LiF-MgF 2 melts is about 0.08-0.38 mol% when the NdF 3 concentration varies from 15 to 30 mol% at 900 ЊC. The solubility increases from 0.13 mol% at 750 ЊC to 0.22 mol% at 900 ЊC in the NdF 3 -LiF eutectic. When MgF 2 is added to NdF 3 -LiF binary melts saturated with Nd 2 O 3 , the Nd 2 O 3 solubility seems to decrease slightly at 30 mol% NdF 3 , while a slight increase was observed with 15 mol% NdF 3 in the binary. When dissolving Nd 2 O 3 in the NdF 3 -LiF eutectic Raman… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
41
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(49 citation statements)
references
References 13 publications
7
41
0
Order By: Relevance
“…The deviation from linearity observed in the LnF 3 -LiF systems indicates the existence of more than two kinds of fluorine environments. This observation is in agreement with the work of Papatheodorou and his co-workers [13,14] using Raman spectroscopy. They have shown that the LnF 3 -AlkF melts (Alk = alkalin) should consist of LnX 3− 6 octahedral species, more or less connected, depending on the LnF 3 content in the melt.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…The deviation from linearity observed in the LnF 3 -LiF systems indicates the existence of more than two kinds of fluorine environments. This observation is in agreement with the work of Papatheodorou and his co-workers [13,14] using Raman spectroscopy. They have shown that the LnF 3 -AlkF melts (Alk = alkalin) should consist of LnX 3− 6 octahedral species, more or less connected, depending on the LnF 3 content in the melt.…”
Section: Resultssupporting
confidence: 92%
“…They are indeed highly corrosive and volatile, and the melting temperatures are high (700-1800 K). Most of the previous work deals with the electrochemical [8,9] and thermodynamic properties [10,11] and very few spectroscopic studies [12][13][14][15] have been done. The latter are important to provide coordination numbers and interatomic distances and are helpful for electrochemical experiment analysis and for building potentials in numerical simulations.…”
Section: Introductionmentioning
confidence: 99%
“…In-situ formation of REF 3 is very important since the solubility of REOs is very low in molten fluorides [20]. Further, an additional advantage is that the formation of rare earth oxyfluoride is likely to be inhibited.…”
Section: Discussionmentioning
confidence: 99%
“…Further, an additional advantage is that the formation of rare earth oxyfluoride is likely to be inhibited. Stefanidaki et al [20] have studied the oxide solubility and Raman spectra of Nd 2 O 3 in the molten alkali fluorides. The authors have reported that the octahedral [NdF 6 ] 3-anion is the dominant complex in the eutectic NdF 3 -LiF melt system.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, the solubility of REO in fluoride melts was widely researched [10][11][12][13][14][15][16][17][18][19][20][21]. It was found that the solubility was relatively low and the melts with high temperature and strong corrosiveness so that there were difficulties for accurate measuring the concentration of REO in fluoride melts.…”
Section: Introductionmentioning
confidence: 99%